Challenges and achievements of integration processes in Africa in light of the new Continental Free Trade Agreement - Danilo Babić (The Review of International Affairs, 2020)
Ever since the African states regained their independence in the second half of the twentieth century, there has been an idea among African political elites about mutual cooperation among their independent states. The spirit of Pan-Africanism was a mainstream discourse within African political, intellectual, and cultural elites throughout the twentieth century. The Pan-African idea was soon concretized into the Organization of African Unity, which was replaced in 2002 by the African Union as we know it today. Yet, despite numerous initiatives, monetary unions, regional economic committees, and the establishment of the African Union as an umbrella organization, the effects of African integration were not good enough. The African Union did not have the strength to impose common policies on all its members, funding remained a permanent problem, and regional economic committees were suffering from the “spaghetti bowl effect” caused by numerous overlaps in membership. Perhaps the biggest problem lies in the fact that African citizens have not been able to feel the benefits of integration, despite sporadic improvements in macroeconomic indicators. New momentum in African integration happened in the spring of 2018 with the launch of a new initiative called the African Continental Free Trade Agreement - AfCFTA. The new agreement differs from the previous agreements in the number of signatories. It has been signed by all countries of the continent (except Eritrea), and it has already been ratified by most of them. The agreement has clear implementation strategies and evaluation criteria. However, we must reexamine whether the new agreement will succeed in overcoming the obstacles that have dulled previous regional initiatives and whether it will succeed in overcoming new obstacles that will emerge in the future.